REPRESENTASI NILAI MORAL PADA FILM PENDEK BAPAK KARYA PANIRADYA KAISTIMEWAN - Muhammad Shahrun Nizam; Anwari Anwari (JOURNAL SAINS STUDENT RESEARCH, 2026)
Film as a communication media acts as an experience and conveyor of moral messages. A film presents a sign or code as a meaning in conveying a message. There are two formulations of the problem in this study, namely: (1) How is the denotative, connotative and mythical meaning in the short film "Bapak" by Paniradya Kaistimewan, and (2) How is the representation of the moral values of the short film "Bapak" by Paniradya Kaistimewan. To answer these problems, this study uses a non-scene qualitative approach. The method used in this study is the Roland Barthes Semiotic analysis method. In this study it can be concluded that the film Bapak by Paniradya Kaistimewan has moral values that are in accordance with Islamic teachings such as the value of simplicity, the value of hard work, the value of compassion, sacrifice, responsibility, hope for the future and gratitude. Communication media such as short films can be an effective means of spreading moral values that are in accordance with Islamic teachings.